The Influence of Transformational Leadership of School Principals, School Culture, and Work Environment on Organizational Citizenship Behavior (OCB) of Early Childhood Teachers in South Arut District, West Kotawaringin Regency - Nor Halimah; Nurtanio Agus Purwanto (Journal of Educational Sciences, 2026)
This study aims to determine the effect of transformational leadership, school culture, and work environment on Organizational Citizenship Behavior or OCB of early childhood teachers in South Arut District, West Kotawaringin Regency. This study uses a quantitative approach with an ex post facto design. The research sample consisted of 178 teachers from 64 PAUD units. Data were collected through a standardized questionnaire that had been tested for validity and reliability, and all items were declared to meet the measurement criteria. Classical assumption tests showed that the regression model met the statistical requirements, so that simple and multiple linear regression analyses could be performed to test the partial and simultaneous effects between variables. The results showed that transformational leadership, school culture, and work environment individually had a positive and significant effect on the OCB of PAUD teachers. Transformational leadership was the most dominant factor in encouraging teachers' extra-role behavior. School culture and work environment functioned as a value system and supporting conditions that strengthened and stabilized this behavior. Simultaneously, the three variables explain a significant proportion of the variation in OCB. In conclusion, inspirational leadership, collaborative culture, and a conducive work environment play an important role in continuously improving the professionalism and voluntary behavior of PAUD teachers in local PAUD units.